Complexes of Copper(II), Nickel(II) and Cobalt(II) withBis(2-hydroxyimino-1-phenylpropylidene)-1,2-diaminobenzene. - SAHU, K.; KUMAR, PRAKASH; KUMAR., MUKESH (Asian Journal of Chemistry, 2010)
A number of metal complexes of the types ML [M = Co(II), Ni(II), Cu(II)], M(H2L)X2 [M = Co(II), Ni(II); X = CI¯, Br¯, I¯ ] and Cu2LX2 (X = CI¯, Br¯ ), where H2L = bis(2-hydoxyimino -1-phenylpropylidene)- 1,2-diaminobenzene have been synthesized and characterized.